Sonographic and Doppler Evaluation of Carotid Artery in Hypertensive and Normotensive Individuals - Harsha Kaur; Rajeev K. Ranjan; Anima R. Xalxo; Nisha Rai; Suresh K. Toppo; Arti Kumari; Rashmi Kumari (Journal of Pharmacy and Bioallied Sciences)
Background: Hypertension is a significant risk factor for cardiovascular diseases. Evaluating arterial distensibility can be inconsistent, but the resistive index (RI) measured by Doppler ultrasound is effective in assessing vascular resistance. IMT and RI are valuable in atherosclerosis evaluation. Methodology: A structured case sheet captured clinical history, physical examination findings, and investigation results. Each participant underwent a bilateral carotid Doppler examination. Group A (100 hypertensive subjects) and Group B (100 normotensive subjects) included individuals aged 40–55 years. Results: When we looked at the intima–media thickness (IMT) of common carotid artery in normotensive people, the mean value was 0.49 mm on the right side and 0.50 mm on the left side. Their resistive index (RI) was 0.56 on both sides. On the other hand, hypertensive individuals had an IMT of 0.97 mm on the right side and 0.96 mm on the left side, with an RI of 0.78 on both sides. It was noted that both IMT and RI were significantly higher in patients with hypertension in comparison to those with normal blood pressure. Conclusion: The results depicted a statistically significant increase in both IMT and RI measurements in hypertensive subjects as opposed to normotensive ones, consistent with the conclusions of various Indian and international studies.